Empowerment Of School Committees In Improving The Quality Of Education Basic Schools Of Indonesia-Malaysia State Border - Muhammad Sahrul; Mawar Mawar; Retnowati WD Tuti; Nida Handayani (Indonesian Journal of Law and Economics Review, 2020)
The purpose of this study is to see how the form of empowerment of school committees in improving the quality of education especially in elementary schools. The research method used is descriptive qualitative approach with data collection techniques namely observation, interviews, and documentation. Research findings The existence of a school committee is an important element in improving the quality of school education services, its existence with all the tasks and functions it has can play a role in realizing better quality education services. Efforts to empower school committees are carried out in various ways although they are still not ideal as stated in the regulations related to school committees. In principle, so far the participation of school committee members and the form of empowerment of school committees is still limited to routine meetings and the fulfillment of supporting facilities for student learning facilities that are done voluntarily by school committees. Based on this, the efforts to empower school committees have been made but are still limited to routine agendas that are not yet optimal as the actual duties and functions of school committees.